2020
DOI: 10.1016/j.jacr.2020.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Variables Influencing Radiology Volume Recovery During the Next Phase of the Coronavirus Disease 2019 (COVID-19) Pandemic

Abstract: The coronavirus disease 2019 (COVID-19) pandemic has reduced radiology volumes across the country as providers have decreased elective care to minimize the spread of infection and free up health care delivery system capacity. After the stay-at-home order was issued in our county, imaging volumes at our institution decreased to approximately 46% of baseline volumes, similar to the experience of other radiology practices. Given the substantial differences in severity and timing of the disease in different geogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
72
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(86 citation statements)
references
References 9 publications
(12 reference statements)
12
72
1
Order By: Relevance
“…Imaging volume at our institution began decreasing sharply starting on March 11th, following a state of emergency being declared in Massachusetts. Similarly, previous studies have shown that imaging volume decreased elsewhere in the country as well, including at institutions in the state of New York and in Santa Clara County, California, all within a week of the observed decrease at our institution (11,14). It was during this time that the WHO declared the COVID-19 outbreak a pandemic; together with subsequent CDC and American College of Radiology recommendations, this led to changes in not only our hospital system policies, but all health care systems across the United States to delay nonessential imaging studies as part of the widespread effort to slow the rate of new infections (10,16,17,20).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Imaging volume at our institution began decreasing sharply starting on March 11th, following a state of emergency being declared in Massachusetts. Similarly, previous studies have shown that imaging volume decreased elsewhere in the country as well, including at institutions in the state of New York and in Santa Clara County, California, all within a week of the observed decrease at our institution (11,14). It was during this time that the WHO declared the COVID-19 outbreak a pandemic; together with subsequent CDC and American College of Radiology recommendations, this led to changes in not only our hospital system policies, but all health care systems across the United States to delay nonessential imaging studies as part of the widespread effort to slow the rate of new infections (10,16,17,20).…”
Section: Discussionsupporting
confidence: 85%
“…Various modalities were differentially affected during the COVID-19 pandemic. Previous studies in New York and Santa Clara demonstrated that mammography and nuclear medicine exhibited the greatest degree of volume reduction (11,14). Similarly, mammography and nuclear medicine also exhibited the greatest level of decrease in our study.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Although we seek to predict the future, models that project rates of service resumption make key assumptions that individual practices must validate for their own situation before implementing system responses. Multiple institutions present their data showing the magnitude and time course for imaging reduction rates that reflect their institution capacity, their local rate of COVID-19 infections, and state-level shelter-in-place regulations [2][3][4][5]. Although the shape of the curve is similar, hyperlocal variables introduce variability.…”
Section: -Alexandre Dumasmentioning
confidence: 99%
“…Although the shape of the curve is similar, hyperlocal variables introduce variability. One institution modeled service recovery informed by hyperlocal considerations [2].…”
Section: -Alexandre Dumasmentioning
confidence: 99%